EFEKTIVITAS LAYANAN KONSELING KELOMPOK DALAM MENINGKATKAN AKHLAK MULIA SISWA KELAS IX DI MTS NOOR AINI BANJARMASIN - Safari, Humaidi; Hamzah, Hamzah; Heiriyah, Ainun (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
Noble character that plays an important role in realizing a life that is understood and dignified. Noble character supports ethics, character, morals as manifestations of religious education. Group counseling service is one of the guidance and counseling services in schools. the field of guidance and counseling services received is effective enough to help students improve and develop good morals and protection at MTS Noor Aini Banjarmasin. The research method used was one group, the pretest-poststest design that is in this study design, first from the group of subjects given a pre-test and then given treatment at a certain time and then measuring back the post-test to compare the situation before and before treatment (Sugiyono ) Based on the results of observations with Guidance and Counseling teachers at MTs Noor Aini Banjarmasin, there was an assessment of IX A class students who discussed about participants who lacked morals, this can be shared with students who have poor moral behavior. This can be seen from the still many students who like to be caught, like cheating, like to participate, do not pay attention to the teacher when giving lessons, always deny winning promises, and even more so about what is spent while spending class hours. The researcher took 20 students or one class for interviews related to students who lacked morals. From the results of the questionnaires given to 20 students, it can be seen that before being given counseling services the group of 6 (six) students entered the criteria of the students. Of the 6 participants who have not been given assistance or care, this shows that the general participants of the students have poor character Based on the results of the pretest, students need to get further training.